HUBUNGAN ANTARA FATHERLESS DENGAN SELF ESTEEM PESERTA DIDIK DI SMAN 1 RANAH PESISIR - Yulia Muslyanti; Wira Solina; Mori Dianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The phenomenon of fatherlessness, the absence of a father figure in a child's life, is increasingly common and impacts students' psychological aspects, including self-esteem. This study aims to describe the condition of fatherlessness, the level of self-esteem, and the relationship between the two in students at SMAN 1 Ranah Pesisir. This study used a quantitative correlational approach with a sample of 62 students taken through a purposive sampling technique. The instrument used was a questionnaire that had been tested for validity and reliability. The results showed that the condition of fatherlessness was in the high category, while self-esteem was in the low category. There was a weak negative relationship between the condition of fatherlessness and self-esteem. These results indicate that the higher the condition of fatherlessness, the lower the level of self-esteem of students. Therefore, it is important for parents, especially fathers, to be physically and emotionally present in their children's lives